Détermination de quelques facteurs de risque liés au développement de l’insuffisance rénale chronique chez des patients de la région de Mostaganem - OURARI, Hafsa (My University, 2020)
End-stage chronic renal disease (ESRD) is a major public health problem. Its support is heavy and restrictive from an economic and social point of view. It is declared in Alegria a major public health priority. This is the result of a steady increase in its incidence and prevalence. The objective of this work is to determine some risk factors linked to the development of CRSD in patients from the Mostaganem region. This study was carried out in 135 patients (sex ratio F / M, 61/74) aged 18 to 89 years with chronic renal failure and treated by hemodialysis at the level of the Public Hospital of Mostaganem. This work is carried out within one month (from February 16 until March 15, 2020). All patients are treated with hemodialysis 4 times a day and each session lasts 4 to 5 hours. Urea and creatinine assay is performed. Our results show that: • Men are more affected by IRCT than women (54, 81% vs. 45, 19%). • In the population studied, the nephropathies involved are mainly arterial hypertension in 48.15% of cases, followed by food coloring and supplements (19, 26%), family history (17, 78%) and diabetes in 9, 63% of cases; 8, 89% of the causes are medication and cholesterol (5, 93%). • An increase in plasma concentrations of urea and creatinine. All of our results show that high blood pressure and food supplements are major causes of end-stage chronic kidney disease.
Keywords: Creatinine; Hemodialysis; End-stage chronic renal failure; Nephropathies; Urea.